Factors that Influence Social Media Marketing Activity and the Effect on Business Performance of The SMEs in Bandung - Syafa Firsta Alika; Teguh Widodo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The extensive use of social media has prompted research on factors influencing its adoption for marketing among SMEs in Bandung and its impact on business performance. Social media has become pervasive and significantly shapes marketing strategies in the digital era. This study investigates factors influencing social media adoption and its effect on business performance. Key variables include perceived usefulness, ease of use, compatibility, cost, social media for marketing, and business performance. Quantitative data selected from 100 SMEs in Bandung. Data were collected via a survey and analyzed using SEM-PLS constructed by 26 questionaire items. A theoretical model has been created by combining elements from TAM and UTAUT2, with certain adaptations, to examine how this impact relates to business performance. Findings reveal that perceived usefulness, ease of use, compatibility, and cost positively influence SMEs' adoption of social media for marketing activities. The study also demonstrates that using social media for marketing positively impacts business performance. Ultimately, promoting sincerity in raising awareness about the benefits of SMM to Indonesian SMEs can encourage its adoption for their overall advantage. Keywords: Perceived Usefulness, Ease of Use, Compatibility, Social Media Marketing, Business Performance